PENDAMPINGAN PENULISAN KARYA TULIS ILMIAH BAGI SISWA/I SMA N 6 YOGYAKARTA - Yayuk Hidayah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Experience with scientific discourse on student growth can inspire innovative assignments and promote applied learning for students. SMA N 6 Yogyakarta is a public school in Yogyakarta which has the motto The Research School Of Jogja. As a school that prioritizes excellence in the form of improving the quality of educational outcomes, SMA N 6 Yogyakarta continues to strive to improve quality, one of which is by assisting in writing scientific papers for its students and students, one of which is through mentoring in writing scientific papers for their students. The purpose of the service activities carried out is an understanding of the important points of scientific writing for class X students of SMA N 6 Yogyakarta. The method of implementing the service is lectures, discussions, and the practice of writing scientific articles. Implementation is divided into three stages, namely preparation, implementation and evaluation. The result of the devotional activity of accompanying the writing of scientific papers for students of SMA N 6 Yogyakarta is an increase in the knowledge of SMA N 6 Yogyakarta students about writing scientific papers, especially about how to research using methods properly and correctly. In addition, the devotional activity of accompanying the writing of scientific papers has also succeeded in being able to learn, test, measure, accurately regarding the direction of their research. Through this mentoring activity, it is a way of developing human resources that can build good social relations and also develop a good personality for students of SMA N 6 Yogyakarta as the young generation of Indonesia. Through this community service activity, the authors conclude that mentoring the writing of scientific papers for students at SMA N 6 Yogyakarta is very beneficial for consistently improving their research abilities because it enriches students' knowledge of comfortable scientific writing